EVALUATION OF THE QUALITY AND PROXIMATE COMPOSITION OF BEEF SOLD AT THE ABATTOIR OF KANO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
This research was aimed at evaluating the pH of beef, as well as its cook loss value and water holding capacity, as well as its proximate composition of the beef from the Kano State abattoir. The proximate composition of the beef was also analyzed using standard procedures described by the Association of the Official Analytical Chemists (AOAC). The beef samples were aseptically obtained from the Kano state abattoir during the month of September when the animals were well fed and healthy, with five cows randomly selected and used for the analysis. The results indicate the pH for the beef to be 5.9, while the cook loss and water-holding capacity were found to be 32.71% and 24.33% respectively. The proximate contents were also reported as follows; protein content (21.50%); fat content (6.75%); ash content (0.92%) and moisture content (68.19%). The results in indicate that all the parameters analyzed for the beef obtained from the Kano abattoir are comparable with the results reported by various researchers, and are all within the standard acceptable limits. Consequently, this impart positive economic implications to the both seller and the consumer, as well as enhancing the meats taste and palatability. The present study concluded that the meat from the Kano State abattoir can be safely consumed by the consumers.
Keywords: Beef, Cook loss, Water-holding capacity, Abattoir, Proximate composition